Dampak Sosial Masyarakat pada Program PKH di Desa Dulupi Kecamatan Dulupi Kabupaten Boalemo - Mifta Khulzannah Saidi; Zuchri Abdussamad; Romy Tantu (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
This research aims to examine the social impact of the implementation of the Family Hope Program (PKH) on the community in Dulupi Subdistrict, Boalemo Regency. The PKH program, as one of the government's efforts to alleviate poverty through conditional social assistance, has various social implications at the village level. The research approach used is descriptive qualitative, with data collection techniques through observation, in-depth interviews, and documentation. Rawls' theory of social justice is used as the analytical framework in this research, with indicators consisting of beneficiary fairness, social eligibility selection, and transparency in social distribution. The research findings indicate that there was inequality in the selection process of PKH beneficiaries, leading to social jealousy among the community. Additionally, the distribution mechanism of assistance was deemed lacking in transparency, resulting in distrust among some people toward the village government. Although this program helps improve access to education and health care for beneficiary families, there were indications of dependency on assistance and weak economic empowerment of the community. Therefore, there is a need for periodic evaluation, improved validation of beneficiary data, and strengthened socialization functions to ensure the program runs more fairly, transparently, and effectively in enhancing sustainable community well-being.